2021
DOI: 10.1101/2021.01.04.20248717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing psychosis risk using quantitative markers of disorganised speech

Abstract: Recent work has suggested that disorganised speech might be a powerful predictor of later psychotic illness in clinical high risk subjects. To that end, several automated measures to quantify disorganisation of transcribed speech have been proposed. However, it remains unclear which measures are most predictive of psychosis-onset, how different measures relate to each other and what the best strategies are to elicit disorganised speech from participants. Here, we assessed the ability of twelve automated Natura… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…However, this assumption has only inconsistently been supported by the literature, with highly varying statistical significance and size of the effects found across studies: while some studies found a strong correlation between semantic coherence and measures of formal thought disorder (Bilgrami et al, 2022;Elvevåg et al, 2007), most others reported uncertain results (Bedi et al, 2015;Haas et al, 2020;Just et al, 2020;Morgan et al, 2021;Pauselli et al, 2018;Sarzynska-Wawer et al, 2021;Tang et al, 2021). Our study emphasized the lack of a clear picture.…”
Section: Globalcontrasting
confidence: 65%
See 1 more Smart Citation
“…However, this assumption has only inconsistently been supported by the literature, with highly varying statistical significance and size of the effects found across studies: while some studies found a strong correlation between semantic coherence and measures of formal thought disorder (Bilgrami et al, 2022;Elvevåg et al, 2007), most others reported uncertain results (Bedi et al, 2015;Haas et al, 2020;Just et al, 2020;Morgan et al, 2021;Pauselli et al, 2018;Sarzynska-Wawer et al, 2021;Tang et al, 2021). Our study emphasized the lack of a clear picture.…”
Section: Globalcontrasting
confidence: 65%
“…However, a critical obstacle to any concrete use of these findings is that it is not clear whether the findings would replicate and generalize to new samples and populations, an overarching problem for clinical and social sciences (Hitczenko et al, 2021;Parola et al, 2020;Rocca & Yarkoni, 2021;Rybner et al, 2021). Indeed, a closer look reveals clearly contradictory results: linguistic measures are inconsistently associated with symptoms, and findings vary across different rating scales and samples (Bedi et al, 2015;Corcoran et al, 2018;Haas et al, 2020;Morgan et al, 2021;Pauselli et al, 2018;Sarzynska-Wawer et al, 2021;Tang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recognition starts with diving deep into an individual's mindset and understanding their emotions. Psychological research [8,15,22,25,26] has found that people's mental states relate to how they communicate; written and spoken language can thus reveal psychological states. A person's emotional state can be anticipated through their communication [22,27]identifying a quantitative coexistence and correlation among emotional words used by an individual can unveil crucial insights into their emotional state [28,29].…”
Section: Literature Review: Cognitive Data Science Mental Well-being ...mentioning
confidence: 99%
“…Speech analysis is an emerging field in mental health research that holds great potential for improving the diagnosis and treatment of various mental disorders Cummins et al, 2015;De Boer et al, 2021;Morgan et al, 2021;Teferra et al, 2022;Wanderley Espinola et al, 2022). By analyzing patterns in language use, such as the use of specific words or the rate of speech, researchers can gain insights into a patient's cognitive and emotional functioning, as well as neural development (Mota, Natália Bezerra, Weissheimer, Finger, Ribeiro, Malcorra, & Hübner, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Most common approaches include the measurement of speech connectivity, which is the way that speech flows and connects to form thoughts and helps evaluate both coherence and syntactic complexity (Mota, Natália B. et al, 2017;Mota, Natália Bezerra et al, 2023;Spencer et al, 2021a) as well as measuring markers of semantic coherence (Bedi et al, 2015;. Evaluating semantic coherence is based on Latent Semantic Analysis (LSA), an approach that captures the distance between words that have been represented in a vectorized space based on their co-occurence in a big text corpus while connectivity is measured applying graph theory on speech, representing all words as nodes and the connection between words as edges (see Methods for more detailed explanation) (Bedi et al, 2015;Morgan et al, 2021;Nettekoven et al, 2023;Spencer et al, 2021b). Former studies utilized these automated markers to identify psychotic disorders, relapse and vulnerability as well as to quantify changes in speechhowever, as did studies did not take cannabis use into account, the effect of cannabis use on these observed changes and classifications remained unexplored.…”
Section: Introductionmentioning
confidence: 99%